2016
DOI: 10.1016/j.ejrad.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic tumor volume and total lesion glycolysis on FDG-PET/CT can predict overall survival after 90Y radioembolization of colorectal liver metastases: A comparison with SUVmax, SUVpeak, and RECIST 1.0

Abstract: Purpose To compare the performance of 4 metrics of metabolic response on FDG-PET/CT against RECIST 1.0 for determining response and predicting overall survival (OS) following 90Y resin microspheres radioembolization of colorectal liver metastases (CLM). Methods We conducted an IRB-waived retrospective review of our radioembolization database to identify patients with unresectable CLM treated between December 2009 and December 2013. We included patients who had both PET/CT and contrast enhanced CT (CECT) avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
3
36
0
2
Order By: Relevance
“…Previous studies have shown the feasibility and value of quantitative SPECT for the evaluation of the extra-and intrahepatic distribution of 90 Y and absorbed dose quantifications after TARE (19). More recently, several studies investigating hepatic metastases found CT perfusion imaging and metabolic response assessment using PET predictive of tumor response early after TARE (20). This study introduces TNR as a quantitative surrogate on SPECT as a readily applicable predictor for enhancement-based tumor response after TARE in HCC (P 5 0.038).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the feasibility and value of quantitative SPECT for the evaluation of the extra-and intrahepatic distribution of 90 Y and absorbed dose quantifications after TARE (19). More recently, several studies investigating hepatic metastases found CT perfusion imaging and metabolic response assessment using PET predictive of tumor response early after TARE (20). This study introduces TNR as a quantitative surrogate on SPECT as a readily applicable predictor for enhancement-based tumor response after TARE in HCC (P 5 0.038).…”
Section: Discussionmentioning
confidence: 99%
“…Shady et al [50] showed that the Response Evaluation Criteria in Solid Tumors 1.1 (RECIST 1.1) have poor sensitivity in this clinical setting and that the Choi criteria or metabolic criteria such as European Organization for Research and Treatment of Cancer or PET Response Evaluation Criteria in Solid Tumors applied to PET with FDG are more relevant. The same group of investigators also showed that metabolic response on FDG PET/CT can predict overall survival [51]. Another group of investigators suggested that dose volume histograms derived from PET/MRI of 90 Y distribution in tumor can be helpful in predicting responders and nonresponders [52].…”
Section: Selective Internal Radioembolization Of Malignant Liver Lesionsmentioning
confidence: 99%
“…It has been demonstrated that areas of high 18 F‐FDG uptake and [1‐ 13 C] lactate production from hyperpolarized [1‐ 13 C] pyruvate did not correlate with each other in a large heterogeneous canine tumor, suggesting that elevated glucose uptake and high lactate production occurs in different tumor regions (Figure ) . There is growing evidence that the assessment of tumor metabolic activity may reflect treatment response more accurately than reduction in tumor size . However, it should be noted that this is not necessarily a measure of long term survival.…”
Section: Hyperpolarized 13c Probes For Carbohydrate Metabolismmentioning
confidence: 99%